Dislocation mechanism of fading of luminescence intensity - Даулетбекова, А.; Скуратов, В.; Маника, И.; Маникс, Я.; Забельс, Р.; Кирилкин, Н.; Акилбеков, А.; Гиниятова, Ш.; Байжуманов, М.; Сейтбаев, А.; Кудайбергенова, С. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Depth profiles of nanohardness and photoluminescence of F2 and F+3 centers in LiF crystals irradiated with 12 MeV 12 С, 56 MeV 40 and 34 MeV 84 Kr ions at fluences 1010 −1015 ions/cm 2 have been studied using laser scanning confocal microscopy, dislocation etching and nanoindentation techniques. The depth-resolved nanohardness measurements and dislocation etching data have shown a remarkable hardening effect and increased concentration of dislocations and other nanodefects in the end-of-range region with dominant contribution of defects formed via elastic collision (nuclear loss) mechanism. The observed fading of luminescence intensity at high fluences is related to intense nucleation of dislocations as sinks for aggregate color centers. An activating role of local stress field of dislocations and other extended defects in the evolution of damage structures is suggested.